Multiuser detection in fast-fading multipath environments. - Sayeed, A.M.
We propose a new framework for multiuser detection in fast-fading channels that are encountered in many mobile communication scenarios. Existing multiuser RAKE receivers, developed to combat multipath fading and multiuser interference in slow fading, suffer substantial degradation in performance under fast fading due to errors in channel state estimation. The detectors proposed in this paper employ a novel receiver structure based on time-frequency (TF) processing that is dictated by a canonical representation of the wide-sense stationary uncorrelated scatterer (WSSUS) channel model. The workhorse of the framework is a TF generalization of the RAKE receiver that exploits joint multipath-Doppler diversity. Analytical and simulated results based on realistic fast-fading assumptions demonstrate that the proposed multiuser detectors promise substantially improved performance compared to existing systems due to the inherently higher level of diversity afforded by multipath-Doppler processing
Keywords: CDMA system; WSSUS channel model; Canonical representation; Channel state estimation; Diversity; Errors; Fast-fading channels; Fast-fading multipath environments; Joint multipath-Doppler diversity; Mobile communication; Multipath-Doppler processing; Multiuser RAKE receivers; Multiuser detection; Multiuser interference; Performance; Receiver structure; Simulated results; Slow fading; Time-frequency processing; Wide-sense stationary uncorrelated scatterer